Cost Estimates for Designing and Implementing a Novel Team Care Model for Chronically Ill Patients. Issue 1 (January 2018) - Panattoni, Laura; Dillon, Ellis; Hurlimann, Lily; Durbin, Meg; Tai-Seale, Ming
Abstract : Little is known about the cost of implementing chronic care models. We estimate the human resource cost of implementing a novel team-based chronic care model "Champion, " at a large multispecialty group practice. We used activity-based costing to calculate costs from development through rollout and stabilization in 1 clinic with 12 000 chronic care patients. Data analyzed included Microsoft Outlook meeting metadata, supporting documents, and 2014 employee wages. Implementation took more than 29 months, involved 168 employees, and cost the organization $2 304 787. Payers may need to consider a mixed-payment model to support the both implementation and maintenance costs of team-based chronic care. Abstract : Supplemental Digital Content is Available in the Text.